Implementation of POE (Predict, Observe and Explain) in Grade 5 Elementary School Students Using KIT Experiments On The Nature of Water (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
The purpose of this study was to provide an overview of student's understanding of the science concept of the nature of water with the application of POE (Predict, Observe and Explain) learning with the accompanying use of KIT in the nature of water. This study uses descriptive method with data collection techniques in the form of observation, interviews and tests. The sample used was grade 5 elementary school students in Bandung. The results showed that as many as 87,5% of students experienced an increase in the understanding of the science concept on the nature of water and 100% of students stated used experimental KIT very enjoyable.